Research on Children’s and Young People’s Tehatre in Spain: State of Play - Muñoz Cáliz, Berta (Talía. Revista de estudios teatrales, 2020)
The purpose of this article is to reflect what has been the situation of research on children’s theater in Spain so far. It offers an overview of studies published from the 1960s to the present day, especially covering repertoires of edited texts, historiographic works and monographic studies on authors, as these have been the paths that scholars of this matter have traveled so far. Likewise, in those aspects that have not yet been sufficiently explored, some of the documentary sources that the researcher can go to undertake future studies on this matter are offered.